Implementasi Modul Digital Kesehatan Mental Berbasis Model PRECEDE–PROCEED Upaya Menurunkan Gejala Depresi Postpartum di Klinik Musytasyfah Karawang - Lastriati Dewi Ayudarista; Byba Melda Suhita (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Introduction: Postpartum depression (PPD) is a major maternal mental health problem, with a global prevalence of 10–17% and approximately 6.1% in Indonesia. Musytasyfah Inpatient Clinic, Karawang, has not yet implemented a structured screening and follow-up system for early PPD detection. A preliminary assessment using the Edinburgh Postnatal Depression Scale (EPDS) among 15 postpartum mothers identified two mothers (13.3%) with EPDS scores ≥10, indicating possible PPD symptoms. Methods: This community service program aims to implement a Digital Maternal Mental Health Module based on the PRECEDE–PROCEED model. The activity employs a health education plan (SAP) integrated with a one-group pre-test post-test design using the EPDS instrument. The target participants are postpartum mothers 14–42 days after delivery. The intervention consists of five learning modules delivered through WhatsApp, face-to-face education sessions, and focus group discussions over four weeks. Program effectiveness will be evaluated using process and outcome indicators, with EPDS scores analyzed using the Wilcoxon Signed-Rank Test. Results: The expected outcomes include baseline data on PPD, improved maternal knowledge, reduced EPDS scores, identification of implementation barriers and facilitators, and evidence regarding the feasibility of the digital module for early PPD prevention and detection. Conclusion: The Digital Maternal Mental Health Module is expected to strengthen early screening, maternal mental health education, and follow-up services while supporting the development of a sustainable standard operating procedure for PPD screening in primary maternal healthcare settings.